8.0k views
5 votes
(08.03 MC)

Solve for x using the Quadratic Formula: x2 - 6x + 9 = 0
-bt/6².
-4ac
X=
2a
A. x = 6
B. x = 3
C. x=1
D. x=0

2 Answers

5 votes

Answer:

x=3

solution,

Rewrite x^2-6x+9 in the form a^2-2ab+b^2 where a=X and b=3.


{x}^(2) - 2(x)(3) + {3}^(2) = 0

Use square of difference,


{(a - b)}^(2) = {a}^(2) - 2ab + {b}^(2) \\ {(x - 3)}^(2) = 0

Take the square root of both sides


x - 3 = 0

Add 2 to both sides,


x - 3 + 3 = 0 + 3 \\ x = 3

hope this helps..

Good luck on your assignment..

User Reiner Gerecke
by
5.4k points
4 votes

Answer:

B. x = 3

Explanation:

You really don't need to quadratic formula for this. It would take too much time. Instead, factor out the equation:

(x -3)(x - 3) = 0

Once you found that, you should see that your roots will equal to 3.

User Daylight
by
6.7k points